An Economic Perspective on Religious Education : Complements and Substitutes in a Human Capital Portfolio - Carmel Ullman Chiswick (Institute for the Study of Labor (IZA), 2005)
This paper models the tradeoffs between education in secular subjects, formal and informal, and the formation of religion-specific human capital. It explores some implications of negative externalities between religious and secular education. Applications include the tension between science and religion during the European Enlightenment and the development of religious education by American Jewry in the 20th century United States. The paper also discusses some implications for the vitality and intergenerational robustness of religious communities.
Keywords: J15; J20; Z12; 330; religion; ethnic groups; education; minorities; Bildungsinvestition; Religion; Humanismus; Externer Effekt; Ethnische Gruppe; Religionsgemeinschaft; Theorie; Vereinigte Staaten